Species identification of Campylobacter jejuni ssp. jejuni and C. coli by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and PCR - Kolínská, R; Drevínek, M; Jakubů, V; Zemlicková, H (Folia microbiologica, 2008)
The Campylobacter species strains (n = 42; isolated from clinical samples and deposited in Czech National Collection of Type Cultures, Prague) originally phenotypically (and biochemically) identified as Campylobacter jejuni were re-classified using molecular biological and mass spectrometric methods. Whole-cell MALDI-TOF MS (matrix-assisted laser desorption/ionization time-of-flight mass spectrometry) separated the isolates into two genetically related strains--C. jejuni (n = 26) and C. coli (n = 16) and, moreover, distinguished the intimate details in the group of tested strains. It also made it possible to create the MALDI-TOF MS dendrogram; similarly, the spectral characteristics were used for the 3D cluster analysis. Polymerase chain reaction (PCR) confirmed the results obtained by mass spectrometry. Both methods (PCR and MALDI-TOF MS) gave the same results which supports their suitability in the rapid and accurate Campylobacter-species determination.
Keywords: Feces; Cats; Campylobacter coli; DNA, Bacterial; techniky typizace bakterií; polymerázová řetězová reakce; Polymerase Chain Reaction; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Bacterial Typing Techniques; kočky; DNA bakterií; zvířata; feces; Humans; Campylobacter jejuni; Species Specificity; spektrometrie hmotnostní - ionizace laserem za účasti matrice; druhová specificita; lidé; Animals